ANALISIS SISTEM DAN PROSEDUR PEMUNGUTAN PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR PADA BADAN PENDAPATAN DAERAH PROVINSI SULAWESI UTARA - Kalalo, Angraini Puspita; Ilat, Ventje; Afandi, Dhullo (Universitas Sam Ratulangi, 2020)
North Sulawesi Province levies five provincial taxes, two of which are PKB and BBN-KB which levied based on the determination of the regional head. This study aims to determine the adequacy of the system and procedures for collecting PKB and BBN-KB in the Province of North Sulawesi. The method used in this research is qualitative. The results of the study showed that the manual payment system and procedures were in accordance with applicable regulation namely Regional Regulation No.7 of 2011 article 52, while for the payment system and procedures through assitive device (dhrive thru) and online were not in accordance with applicable regulation. Then for the internal control analysis system of the procedures for collecting PKB and BBN-KB carried out by BAPENDA, North Sulawesi Province is in accordance with the apllicable internal control concept.